2007
DOI: 10.1186/ar2327
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasonography, magnetic resonance imaging, radiography, and clinical assessment of inflammatory and destructive changes in fingers and toes of patients with psoriatic arthritis

Abstract: The aim of the present study was to assess ultrasonography (US) for the detection of inflammatory and destructive changes in finger and toe joints, tendons, and entheses in patients with psoriasis-associated arthritis (PsA) by comparison with magnetic resonance imaging (MRI), projection radiography (x-ray), and clinical findings. Fifteen patients with PsA, 5 with rheumatoid arthritis (RA), and 5 healthy control persons were examined by means of US, contrast-enhanced MRI, x-ray, and clinical assessment. Each jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
94
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(115 citation statements)
references
References 21 publications
(37 reference statements)
13
94
1
7
Order By: Relevance
“…Generally, the reading reliability was good but with less satisfactory results for acquisition reliability [3,4,23,25,32,34,38,41,44,47,48,51,54,55,61,65,73].…”
Section: Omeract Filter Us Discrimination Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the reading reliability was good but with less satisfactory results for acquisition reliability [3,4,23,25,32,34,38,41,44,47,48,51,54,55,61,65,73].…”
Section: Omeract Filter Us Discrimination Capacitymentioning
confidence: 99%
“…The scoring systems are used for diagnostic purposes [4,25,47] or for responsivness evaluation [48][49][50]. Some authors proposed semiquantitative grading systems based on grey scale modifications with or without, including PD changes, others developed quantitative scores proposing a cutt off value for differentiating between SpA patients and controls.…”
Section: Ultrasound Scoring Systems For Enthesitismentioning
confidence: 99%
See 1 more Smart Citation
“…In particular bone erosion and bone proliferation, which were absent in RA, were seen in 4% and 13% of PsA patients, respectively. Tendon insertion abnormalities were also found more frequently in PsA [7].…”
mentioning
confidence: 84%
“…With US one can quantitatively assess the morphologic (synovial thickness) and functional (blood flow) changes of joints during inflammatory arthritis (1)(2)(3)(4). Several studies have shown that US is a sensitive instrument for depicting synovial inflammation in patients with RA (5,6).…”
mentioning
confidence: 99%